Supplemental thymol and carvacrol increases ileum Lactobacillus population and reduces effect of necrotic enteritis caused by Clostridium perfringes in chickens - Dafei Yin (Nature Portfolio, 2017)
Abstract Necrotic enteritis (NE) caused by Clostridium perfringens is one of the most detrimental infectious diseases in poultry. This study examined the effect of blends of essential oils (BEOs) (25% thymol and 25% carvacrol) on NE and bacterial dynamics and functions in chicks challenged with C. perfringens. Chicks were assigned to a Control diet and BEOs diet (Control diet + 120 mg/kg BEOs), were challenged with C. perfringens from days 14 to 20 and were killed on day 21 for assessment. Supplementation with BEOs decreased the mortality, alleviated gut lesions, and decreased the virulence factors of pathogenic bacteria (VF 0073-ClpE, VF0124-LPS, and VF0350-BSH). Lack of supplementation also changed the nutrient and immunological dynamics of host microbiota in responding to C. perfringens infection. Adding BEOs changed the host ileum microbial population by increasing the numbers of Lactobacillus crispatus and Lactobacillus agilis, and decreasing Lactobacillus salivarius and Lactobacillus johnsonii. The functional roles of these changing host bacterial populations coupled with the putative reduced pathogenicity of C. perfringens by BEOs contributed to the reduction in gut lesions and mortality in infected chickens. It suggests that dietary supplementation with BEOs could significantly reduce the impact of NE caused by C. perfringens on broilers.